Analysis of Chinese and U.S. soy markets and trade dynamics - Zhu, Yuefeng, author; Thilmany, Dawn D., advisor; Pendell, Dustin L., committee member; Pena, Anita Alves, committee member (Colorado State University. Libraries, 2012)
The stable soybean (and soy product) trade relationship between the U.S. and China is threatened by various market factors. This thesis analyzes the drivers behind soybean trade between the U.S. and China. The economic models are constructed and estimated by Seemingly Unrelated Regressions (SURs) to discover what factors may be influencing U.S. domestic soybean (and soy product) demand, as well as factors influencing U.S. export volumes and China import volumes. Discussion of policy implications will be provided based on the estimation results.
Keywords: China; U.S.; trade; soy product; soybean